2004
DOI: 10.1038/sj.onc.1207372
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus oncogenesis and the ubiquitin–proteasome system

Abstract: Epstein-Barr virus (EBV), a human herpesvirus associated with lymphoid and epithelial cell tumors, encodes several proteins that exploit the ubiquitin-proteasome system to regulate latency and allow the persistence of infected cells in immunocompetent hosts. Further modifications of ubiquitin-dependent proteolysis by activated cellular oncogenes contribute to malignant transformation. A detailed understanding of these processes may lead to the development of new therapeutic strategies for EBVassociated cancers. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 115 publications
1
44
0
Order By: Relevance
“…The results are completely in line with the previous report that constitutively activated NF-kB has shown to maintain high expression levels of Bcl-X L and FLIP L/S and confer resistance to some anticancer drugs (Wang et al, 1999;Karin, 2006). EBVassociated gene products like EBNA1 and LMP1 were reported to modify the ubiquitin -proteasome activity and affect proteolysis of various cellular proteins including NF-kB (Masucci, 2004). In addition, EBERs appear to be involved in modulation of cellular response and were reported to activate NF-kB-signalling pathway (Nambo and Takada, 2002;Samanta et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…The results are completely in line with the previous report that constitutively activated NF-kB has shown to maintain high expression levels of Bcl-X L and FLIP L/S and confer resistance to some anticancer drugs (Wang et al, 1999;Karin, 2006). EBVassociated gene products like EBNA1 and LMP1 were reported to modify the ubiquitin -proteasome activity and affect proteolysis of various cellular proteins including NF-kB (Masucci, 2004). In addition, EBERs appear to be involved in modulation of cellular response and were reported to activate NF-kB-signalling pathway (Nambo and Takada, 2002;Samanta et al, 2006).…”
Section: Discussionsupporting
confidence: 91%
“…Many pathogens, such as DNA tumor viruses, encode proteins that mimic, block, or redirect the activity of the ubiquitin-proteasome machinery to modify the cellular environment and protect infected cells from host immune attack (50). EBV encodes several proteins that exploit the host ubiquitin system to regulate its latency and persistence in the host cell (20,(50)(51)(52)(53). For example, EBNA1 resistance to ubiquitination-dependent degradation creates a perfect camouflage to prevent recognition by the host immune system (50).…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has shown that Epstein-Barr nuclear antigen 1 itself may block proteasomal processing [for a review, see ref. [7]]. Consistent with the original hypothesis that EBV mediates resistance to proteasome inhibitors, an earlier study [8] had shown that a panel of lymphoblastoid cell lines was sensitive to inhibitors of the proteasome, whereas most BL cell lines were resistant.…”
Section: Introductionmentioning
confidence: 71%